2007
DOI: 10.1159/000107434
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Rehabilitation in Individuals with Inner-Ear Dysfunction: A Pilot Study

Abstract: A randomised control prospective study was carried out examining patient outcomes after performing a 10-week vestibular home exercise programme. Thirty-two adults with vestibular dysfunction who reported vestibular symptoms negatively affecting daily life were enrolled. Test subjects were provided with an individualised vestibular rehabilitation programme designed by a physiotherapist. Control subjects received a set of strength and endurance exercises only. All subjects performed their exercises 3 times a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…34,35 However, without access to vestibular rehabilitation facilities, balance deficits persist. 36 There were some limitations to this retrospective study.…”
Section: Median Hearing Loss (Dbhl)mentioning
confidence: 99%
“…34,35 However, without access to vestibular rehabilitation facilities, balance deficits persist. 36 There were some limitations to this retrospective study.…”
Section: Median Hearing Loss (Dbhl)mentioning
confidence: 99%
“…After the title and abstract screening, 28 studies were identified as potentially eligible. However, after full text screening, 19 studies were excluded due to the following reasons: sample outside the pre-specified age range (n=14) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] , lack of randomization (n=4) [22][23][24][25] , and sample with no complaints or vestibular disorders (n=1) 26 . Thus, nine randomized controlled trials were eligible for inclusion in this review and had their content critically analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…We did not assess long-term effects but patients that were handed out a booklet about self-management of VR exercises reported fewer vertigo-related symptoms at the 1-year follow up in comparison with patients allocated to routine care (Yardley et al, 2012). In a study by Enticott et al (2008), the control group received the same instructions as the intervention group about the importance of regular daily exercise and weekly walking. The intervention group also received individualized exercises.…”
Section: The Effect Of the Interventionmentioning
confidence: 99%
“…Of those that do exist, the majority indicate that vestibular rehabilitation (VR) improves symptoms and dizziness-related handicaps and increases postural stability in patients with severe vestibular dizziness (Enticott, Vitkovic, Reid, O'Neil, & Paine, 2008;Giray et al, 2009;Yardley et al, 2004). Nursing interventions in general that educate patients to facilitate adherence to treatment are common (Frich, 2003;Suhonen, V€ alim€ aki, & Leino-Kilpi, 2008).…”
Section: Introductionmentioning
confidence: 99%